الجريمة الدولية في ظل أحكام القانون الدولي الجزائي - عزوز عبد القادر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
إن الجريمة الدولية تعتبر من الموضوعات الحيوية المهمة, فهي تمثل تحديّاً وتمرداً على النظام القانوني الدولي لكونها تقع على مصالح وقيم تهم المجتمع الدولي الذي يحرص على حمايتها, ولكن دائماً كانت تبرز صعوبات في تقنين الجرائم الدولية إلى أن جاء نظام روما الأساسي 1998 الذي أنشأ المحكمة الجنائية الدولية حيث حدد أنواع الجرائم الدولية بشكل حصري بِـ ( جريمة الإبادة الجماعية, الجرائم ضد الإنسانية, جرائم الحرب, جريمة العدوان ) وقد حاول البحث تحديد أركان وصور هذه الجرائم الدولية من خلال استعراض وتحليل أهم جهود فقهاء القانون الدولي وأحكام القضاء الجزائي الدولي المؤقت وصولاً إلى وضع نظام روما الأساسي 1998 الذي أنشأ قضاء جزائي دولي دائم ( المحكمة الجنائية الدولية ICC ) . International crime is one of the most vital issues. It represents a challenge and a rebellion against the international legal order because it is based on interests and values ​​of concern to the international community, but it has always been difficult to codify international crimes until the Rome Statute of 1998 establishing the Criminal Court (Crimes of genocide, crimes against humanity, war crimes and the crime of aggression). The elements and forms of these international crimes have been identified through a review and analysis of the most important efforts of scholars of international law and the provisions of the Interim International Criminal Court To develop a 1998 Rome Statute, which established a permanent international penal spend (the International Criminal Court, ICC. (